2009
DOI: 10.1507/endocrj.k08e-340
|View full text |Cite
|
Sign up to set email alerts
|

A Tryptamine Derivative, SST-VEDI-1, Inhibits Apoptosis and Stimulates Mineralization in Osteoblasts

Abstract: Abstract. ssT-VEdi-1(VEdi-1) is a new synthetic compound that is synthesized from tryptamine, and has structural similarity to the ssh-BM family of compounds. however, the biological effects of VEdi-1 have yet to be well characterized. a recent report has demonstrated that ssh-BM-type compounds can stimulate osteoblast activity in cultured scales of goldfish. In this study, we examined the effects of VEDI-1 on osteoblastic differentiation as well as its effects on apoptosis, which is known to be closely relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…For example, parathyroid hormone (PTH) regulates the osterix expression predominantly through cAMP-dependent protein kinase A (PKA) signaling in osteoblast-like cells (27) and the overexpression of PKA inhibitor γ (PKIγ) suppressed the OSX expression in C2C12 cells (34). In addition, SST-VEDI-1, which is also a tryptamine derivative and has a similar chemical structure to that of SSH-BM-I, regulates cAMP level (28). Based on the findings of these reports, it is therefore possible that the cAMPdependent signaling pathway via TAAR1 may act on the SSH-BM-I-mediated osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…For example, parathyroid hormone (PTH) regulates the osterix expression predominantly through cAMP-dependent protein kinase A (PKA) signaling in osteoblast-like cells (27) and the overexpression of PKA inhibitor γ (PKIγ) suppressed the OSX expression in C2C12 cells (34). In addition, SST-VEDI-1, which is also a tryptamine derivative and has a similar chemical structure to that of SSH-BM-I, regulates cAMP level (28). Based on the findings of these reports, it is therefore possible that the cAMPdependent signaling pathway via TAAR1 may act on the SSH-BM-I-mediated osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…Previously, we newly synthesized several compounds containing MS-IPA1 from tryptamine (3). Some of these compounds exhibited an inhibitory effect on apoptosis of osteoblasts (8). In addition, it has been reported that SSH-BM-I, which is also synthesized from tryptamine and has a similar chemical structure to MS-IPA1, increases osteoblast number in the scales of gold fish (9).…”
Section: Discussionmentioning
confidence: 99%
“…A previous report has proposed the hypothesis that a tryptamine compound is metabolized in our body to the corresponding tryptamine derivatives such as SST-VED-I-1, and its biological activity can be modified to become stronger than or different from the original tryptamine compound (7). In fact, recently, we demonstrated that SST-VED-I-1 inhibits starvation-induced apoptosis in osteoblasts, although the original tryptamine compound does not have such an effect (8).…”
Section: Introductionmentioning
confidence: 89%